2018
DOI: 10.1038/s41433-017-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Are we ready for genetic testing for primary open-angle glaucoma?

Abstract: Following a dramatic reduction in the cost of genotyping technology in recent years, there have been significant advances in the understanding of the genetic basis of glaucoma. Glaucoma patients represent around a quarter of all outpatient activity in the UK hospital eye service and are a huge burden for the National Health Service. A potential benefit of genetic testing is personalised glaucoma management, allowing direction of our limited healthcare resources to the glaucoma patients who most need it. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
0
27
0
3
Order By: Relevance
“…However, currently known (nongenetic) risk factors are not strong enough to allow for screening limited to high-risk groups, as too many cases would be overlooked 101,119 Similarly, the currently known genes (from GWAS and other techniques) do not explain the observed heritability completely, and as such, screening based on genes is currently considered premature as well. 57 Knowledge on heritability drives further gene finding (aiming to annihilate the discrepancy between heritability and variance explained by known genes), ultimately aiming for efficient screening and personalized health care based on genetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…However, currently known (nongenetic) risk factors are not strong enough to allow for screening limited to high-risk groups, as too many cases would be overlooked 101,119 Similarly, the currently known genes (from GWAS and other techniques) do not explain the observed heritability completely, and as such, screening based on genes is currently considered premature as well. 57 Knowledge on heritability drives further gene finding (aiming to annihilate the discrepancy between heritability and variance explained by known genes), ultimately aiming for efficient screening and personalized health care based on genetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, genetic and genomic studies have shown encouraging evidence for a possible genetic contribution to the pathogenesis of glaucoma. Starting with studies of single-gene variants, genetic analysis has expanded to whole exome sequencing (WES), genome-wide association studies (GWAS), and genetic/polygenic risk scoring (G/PRS) as methods to illuminate the possible genetic RFs underlying glaucoma [ 28 , 29 ]. These studies have largely painted a picture of glaucoma as a disease that follows a complex inheritance pattern, indicating the importance of underlying genetic variants as a key to disease pathogenesis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because an individual's genetic profile is set at birth, and therefore because risk for disease could theoretically be determined prior to (most) environmental exposures (Wray, Yang, Goddard, & Visscher, ), a great deal of hope has been invested into developing these models as an advancement of precision medicine. However, for many complex diseases, it is debatable whether genomic profiling is ready for clinical use (e.g., Cooke Bailey, Hoffman, et al., ; Cooke Bailey, Loomis, et al., ; Jakobsdottir, Gorin, Conley, Ferrell, & Weeks, ; Khawaja & Viswanathan, ; Schork, Schork, & Schork, ). Family history is typically seen as a good proxy for genetic risk as it reflects shared genetic and environmental factors and thus is incorporated into clinical history when possible for genetic diseases (reviewed in Wray et al., ).…”
Section: Introductionmentioning
confidence: 99%